1997
DOI: 10.1074/jbc.272.14.8946
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Coiled-Coil Interactions within the Kinesin Neck Region Using Synthetic Peptides

Abstract: Kinesin is a dimeric motor protein that can move for several micrometers along a microtubule without dissociating. The two kinesin motor domains are thought to move processively by operating in a hand-over-hand manner, although the mechanism of such cooperativity is unknown. Recently, a ϳ50-amino acid region adjacent to the globular motor domain (termed the neck) has been shown to be sufficient for conferring dimerization and processive movement. Based upon its amino acid sequence, the neck is proposed to dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
98
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(107 citation statements)
references
References 57 publications
7
98
2
Order By: Relevance
“…However, the charged residue found at the d position in the EKEK sequence (see Fig. 1 A) acts in an extremely destabilizing manner within a canonical coiled coil (9,21). Consequently, the observed overall stability of segment I may only be achieved if the low stability of the EKEK region is overcompensated by the hydrophobic collar.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the charged residue found at the d position in the EKEK sequence (see Fig. 1 A) acts in an extremely destabilizing manner within a canonical coiled coil (9,21). Consequently, the observed overall stability of segment I may only be achieved if the low stability of the EKEK region is overcompensated by the hydrophobic collar.…”
Section: Resultsmentioning
confidence: 99%
“…Kinesin-1's neck coiled coil contains highly unconventional sequence elements (9,10) that seem to be conserved in Kinesin-1 motor proteins from bilateral animals ( Fig. 1A) (11).…”
mentioning
confidence: 99%
“…Recent work with peptides from the neck region has established that such uncoiling of the NH 2 -terminal half of the neck can occur (4,5). Although the exact oligomeric state of the complex between the tail and head/neck is not known, the interaction between monomeric DKH365 and GST893-975 suggests that formation of a 4-helix bundle is not necessary, at least for the NH 2 -terminal half of the neck.…”
Section: Discussionmentioning
confidence: 99%
“…There is a likely hinge at position ϳ400 that marks the boundary between the neck and the stalk. Peptides from the neck (4,5) and stalk (6) have been demonstrated to interact in a coiled-coil manner by several criteria. The crystal structure of a dimeric head plus neck construct has been recently determined (7) and it directly demonstrates the coiled-coil interactions in the neck region.…”
mentioning
confidence: 99%
“…The neck and its link to the head are important for the determination of the directionality of movement (Henningsen and Schliwa, 1997;Case et al, 1997;Endow and Waligora, 1998). The neck of animal kinesins has been found to form a coiled-coil (Kozielski et al, 1997;Morii et al, 1997;Tripet et al, 1997) and to be involved in kinesin's processivity (Romberg et al, 1998), while both the neck and hinge have been shown to play a role in mechanochemical coupling (Grummt et al, 1998).…”
mentioning
confidence: 99%